Acetylation of BcHpt Lysine 161 Regulates Botrytis cinerea Sensitivity to Fungicides, Multistress Adaptation and Virulence - Yang, Qianqian (Front Microbiol, 2020)
BcHpt is a core element of the high-osmolarity glycerol (HOG) transduction pathway in Botrytis cinerea. In contrast to other elements of the pathway, which have been characterized and proven to play important roles in vegetative differentiation, fungicide resistance, the multistress response, and virulence in B. cinerea, BcHpt (Histidine-containing phosphotransfer) is essential but uncharacterized in B. cinerea. Our previous study reported the first lysine acetylation site (Lys161) in BcHpt. In this study, the functions of this lysine acetylation site in BcHpt were characterized using site-directed mutagenesis. To mimic Lys161 acetylation, we generated the mutant strain ΔBcHPt + BcHpt(K161Q)-GFP, which exhibited a slower growth rate; lower pathogenicity; higher sensitivity to multiple stresses, including osmotic and oxidative stresses, dicarboximides, and demethylation inhibitors (DMIs); and lower BcSak1 phosphorylation levels than wild-type B. cinerea. Constitutive acetylation of BcHpt Ly161 apparently inhibits hyphal growth, the multistress response, and sensitivity to fungicides in B. cinerea. Moreover, the lysine acetylation site affected phosphorylation of the MAPK BcSak1.